IL‐1Ra deficiency accelerates intervertebral disc degeneration in C57BL6J mice. Issue 2 (23rd April 2022) - Swamy, Ganesh; Salo, Paul; Duncan, Neil; Jirik, Frank; Matyas, John
Abstract: The expression of Interleukin‐1ß (IL‐1ß) and its antagonist and Interleukin‐1 receptor antagonist (IL‐1Ra) are correlated with greater human intervertebral disc (IVD) degeneration, suggesting that elevated IL‐1β activity promotes disc degeneration. Many in vitro studies support such a mechanistic relationship, whereas few in vivo investigations have been reported. The present study tests the effect of increased IL‐1β activity on intervertebral disc in mice with an IL‐1Ra gene deletion. IL‐1Ra−/− mice and wild‐type (WT) C57Bl6J mice were examined at 3 and 12 months of age. Caudal IVD segments were evaluated for disc degeneration by histopathology, functional testing, and inflammatory gene expression relevant to IL‐1β pathways. To test differences in injury response, pinprick annular puncture was performed on IL‐1Ra−/− and WT mice and evaluated similarly. IL‐1Ra−/− IVDs had significantly worse histopathology at 3 months compared to WT controls, but not at 12 months. IL‐1Ra−/− IVDs exhibited significantly more viscous mechanical properties than WT IVDs. qPCR revealed downregulation of inflammatory genes at 3 and 12 months in IL‐1Ra−/− IVDs, with concomitant downregulation of anabolic and catabolic genes. Annular puncture yielded no appreciable differences between 2‐week and 6‐week post‐injured WT and IL1‐Ra−/− IVDs in histopathology or biomechanics, but inflammatory gene expression was sharply downregulated in IL‐1Ra−/− mice at 2 weeks, returning by 6 weeks post injury. In the present study, IL‐1Ra deletion resulted in increased IVD histopathology, inferior biomechanics, and transiently decreased pro‐inflammatory cytokine gene expression. The histopathology of IL‐1Ra−/− IVDs on a C57BL/6J background is less severe than a previous report of IL1Ra−/− on a BALB/c background, yet both strains exhibit IVD degeneration, reinforcing a mechanistic role of IL‐1β signaling in IVD pathobiology. Despite a pro‐inflammatory environment, the annular puncture was no worse in IL‐1Ra−/− mice, suggesting that response to injury involves pathways other than inflammation. Overall, this study supports the hypothesis that IL‐1β‐driven inflammation is important in IVD degeneration. Abstract : IL‐1Ra−/− IVDs had significantly worse histopathology at 3‐months compared to WT controls, but not at 12‐months.